2009
DOI: 10.1002/ejic.200801122
|View full text |Cite
|
Sign up to set email alerts
|

Elongated Titanate Nanostructures and Their Applications

Abstract: Recent advances in the synthesis, characterisation and applications of elongated titanate and TiO2 nanostructures (including nanotubes, nanofibres and nanorods) are reviewed. The physicochemical properties of nanostructures, such as high surface area, efficient ion‐exchange properties, electron and proton conductivity and high aspect ratio, are described in connection with a particular application. Practical aspects of the preparation, stability and transformation of elongated titanates are considered. A criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
171
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(173 citation statements)
references
References 210 publications
(272 reference statements)
0
171
0
2
Order By: Relevance
“…[41] Titanate nanotubes decorated with dye molecules have potential application in dye sensitized solar cells. In typical cell manufacturing processes, the suspension of nanotubes is deposited on the surface of electro-conductive glass followed by calcination at 450 • C. Such high-temperature thermal treatments results in structural and morphological changes of nanotubes, [5,42] which may affect the affinity of dye molecules for the surface of the semiconductor.According to recent reports, [43] annealing of protonated titanate nanotubes (H-TiNT) at 400 • C results in a 34% decrease of their specific surface area, accompanied by loss of water molecules and transformation of titanates to monoclinic TiO 2 (B), [42] maintaining nanotubular morphology. Analysis of MB adsorption isotherm on the surface of annealed samples have revealed that calcination of protonated nanotubes in air at 400 • C for 24 h results in ∼30% decrease of the amount of MB molecules forming the monolayer on the surface of nanotubes (a s ) and 75% decrease of adsorption constant K L ( Table 1).…”
Section: Estimation Of Mb Surface Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Titanate nanotubes decorated with dye molecules have potential application in dye sensitized solar cells. In typical cell manufacturing processes, the suspension of nanotubes is deposited on the surface of electro-conductive glass followed by calcination at 450 • C. Such high-temperature thermal treatments results in structural and morphological changes of nanotubes, [5,42] which may affect the affinity of dye molecules for the surface of the semiconductor.According to recent reports, [43] annealing of protonated titanate nanotubes (H-TiNT) at 400 • C results in a 34% decrease of their specific surface area, accompanied by loss of water molecules and transformation of titanates to monoclinic TiO 2 (B), [42] maintaining nanotubular morphology. Analysis of MB adsorption isotherm on the surface of annealed samples have revealed that calcination of protonated nanotubes in air at 400 • C for 24 h results in ∼30% decrease of the amount of MB molecules forming the monolayer on the surface of nanotubes (a s ) and 75% decrease of adsorption constant K L ( Table 1).…”
Section: Estimation Of Mb Surface Densitymentioning
confidence: 99%
“…Nanotubular titanates, which were originally discovered by Kasuga et al [4] can be potentially used in applications [5] such as catalysis, [6,7] photocatalysis [8,9] and electrocatalysis, hydrogen storage, [10,11] lithium batteries, [12,13] and solar cells. [14,15] The open, mesoporous morphology, high aspect ratio combined with good ion-exchange properties [16,17] and moderate electroconductivity render nanostructured titanates useful in nanoscale design.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are synthesized by various techniques, however the alkaline hydrothermal method is regarded as the most attractive because of its simple procedures and low cost [6]. Nonetheless, the mechanism of nanostructured titanate materials formation and the method providing the control of morphology (specific shape of material, diameter and length, size distribution) are still the subject of intense research efforts [7]. What is more, our literature survey shows that authors describing titanate structures formed through alkaline hydrothermal treatment have used terms nanoribbons, nanowires, nanorods, nanofibers, nanobelts interchangeably [8].…”
Section: Introductionmentioning
confidence: 99%
“…Titania nanotube is expected to be a high performance photocatalyst, because titania nanotube has a large surface area, high adsorption ability with ion exchange capacity and superior charge transport property (Bevykin and Walsh, 2009;Herández-Alonso et al, 2011). Kasuga et al (1998) discovered a simple synthetic method for the preparation of titanate nanotubes.…”
Section: Introductionmentioning
confidence: 99%